The Role of Marketing Management in Information Industry: Corporate Image, Brand Awareness and Promotion (Case Study at PT Lensa Potret Mandiri) - Farhan Saputra; Franciscus Dwikotjo Sri Sumantyo (Universitas Dinamika, 2022)
This article discusses the Role of Marketing Management in the Information Industry: Corporate Image, Brand Awareness and Promotion (Case Study at PT Lensa Potret Mandiri). This study uses quantitative methods and uses IBM SPSS 27 in analyzing the data. The population in this study were 119 respondents with a total sample of 40 respondents. In determining the research sample, the researcher used a sampling technique, namely Simple Random Sampling. Data obtained from questionnaires made on google form and then distributed to respondents using a Likert scale measurement scale. The tests carried out in this study are Validity and Reliability Test, T test, F test and Coefficient of Determination Test. The results of this study are: 1) Corporate image has a significant effect on the Role of Marketing Management partially; 2) Brand awareness has a significant effect on the Role of Marketing Management partially; 3) Promotion has an effect on the Partial Role of Marketing Management; and 4) corporate image, brand awareness, and promotion influence the role of marketing management simultaneously.